CORPUS LINGUISTICS: POTENTIALS AND LIMITATIONS - Kamariah Yunus (UAD TEFL International Conference)
In this digital era, the role of computer technology as a resource for instruction of foreign language learners is increasing as educators recognise the ability of computer technology to produce both independent and collaborative learning environments. Computer technologies, for example the Internet, multimedia, and hypermedia have been introduced in English Language Learning and Teaching (ELLT) to foster language learning process, all of which fall under the category of Computer-Assisted Language Learning (CALL). Corpus linguistics is a systematic analysis of the actual (real) production of language (either spoken or written), in which texts are assembled using computer technology (concordancer) to form a large collection of authentic texts, called a corpus (plural-corpora) that comes in various sizes.  Despite immense research on corpus linguistics in these recent decades, the potentials and limitations of Data-Driven Learning (DDL), the application of corpus linguistics in ELLT have not been widely discussed. Hence, this paper aims to review the potentials and limitations of DDL as a means of opening up opportunities for further studies. This insightful information is highlighted as a means of promoting DDL and producing independent learners in the 21st century classroom.